1997
DOI: 10.1180/minmag.1997.061.409.02
|View full text |Cite
|
Sign up to set email alerts
|

Weathering of ultramafic rocks and element mobility at Mt. Prinzera, Northern Apennines, Italy

Abstract: The weathering of the Mt. Prinzera serpentinites (Parma province, Northern Apennines, Italy) produced dominant smectite and minor Fe-hydroxides. The mobility of the elements during weathering has been estimated using the ratio Ki = MiS/MiR, where Mi indicates the mass of a generic component i before (R) and after (S) the weathering, and using TiO2 as a practically immobile component. For prevalently to tendentially mobile elements, the degree of mobility, which in our case increases as Ki decreases, is in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…The mobility and redistribution of elements within the secondary environment have been widely used to estimate the degree of weathering and the behaviour of elements during weathering (Beyala et al, 2009). Venturelli et al (1997) suggested that reliable information on element mobility during weathering may be obtained by quantitative mass balance approaches. In most mass balance models, one or more elements are isolated and assumed to be immobile (Anderson et al, 2002;Brimhall and Dietrich, 1987;Brimhall et al, 1985;Nesbitt and Young, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…The mobility and redistribution of elements within the secondary environment have been widely used to estimate the degree of weathering and the behaviour of elements during weathering (Beyala et al, 2009). Venturelli et al (1997) suggested that reliable information on element mobility during weathering may be obtained by quantitative mass balance approaches. In most mass balance models, one or more elements are isolated and assumed to be immobile (Anderson et al, 2002;Brimhall and Dietrich, 1987;Brimhall et al, 1985;Nesbitt and Young, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Investigations on surface waters in ultramafic rock and/ or gabbro catchments have been carried out by, e.g., Barnes & O'Neil (1969), Barnes et al (1978), Clark & Fontes (1990), Gascogne & Kamieni (1993), Drever (1997), Venturelli et al (1997), Zedef et al (2000), Zakharova et al (2007), Zhou (2010), Chavagnac et al (2013) and Bucher et al (2015). Typical waters from ultramafic rock terrains are Mg-HCO 3 type waters with elevated pH values.…”
Section: Introductionmentioning
confidence: 99%
“…After considering possible immobile elements in the references consulted (Kurtz et al, 2000;Tapia et al, 1998;Nesbitt and Markovics, 1997;Venturelli et al, 1997), and observing the behaviour of the immobile elements (Fig. 3), those elements that always showed a near zero balance, i.e.…”
Section: Soil Geochemistrymentioning
confidence: 99%
“…not significant) balance. We obtained the element mass balance by applying the formula below (1) (Kurtz et al, 2000;Tapia et al, 1998;Venturelli et al, 1997;Bain et al, 1993;Nesbbit, 1979;Nesbitt and Markovics, 1997). The term Xn is positive when there is a gain of an element in the soil, and negative if there has been a loss of an element with respect to its content in the parent material, and compared to the content of an immobile element.…”
Section: Soil Geochemistrymentioning
confidence: 99%
See 1 more Smart Citation